2006
DOI: 10.1140/epjb/e2006-00175-0
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics and Vlasov equation allow for a simplified Hamiltonian description of Single-Pass Free Electron Laser saturated dynamics

Abstract: A reduced Hamiltonian formulation to reproduce the saturated regime of a Single Pass Free Electron Laser, around perfect tuning, is here discussed. Asymptotically, Nm particles are found to organize in a dense cluster, that evolves as an individual massive unit. The remaining particles fill the surrounding uniform sea, spanning a finite portion of phase space, approximately delimited by the average momenta ω+ and ω−. These quantities enter the model as external parameters, which can be self-consistently determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 14 publications
1
54
0
2
Order By: Relevance
“…First, we intend to implement the computed control term in the framework of the original N-body self-consistent picture and explore possible beneficial effects for the evolution of the radiation field. Further, it is planned to apply the above technique to the case of the reduced Hamiltonian of [2,3]. We point out that an experimental test of the control method on a modified Travelling Wave Tube has been done [10] in absence of self-consistency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we intend to implement the computed control term in the framework of the original N-body self-consistent picture and explore possible beneficial effects for the evolution of the radiation field. Further, it is planned to apply the above technique to the case of the reduced Hamiltonian of [2,3]. We point out that an experimental test of the control method on a modified Travelling Wave Tube has been done [10] in absence of self-consistency.…”
Section: Resultsmentioning
confidence: 99%
“…Such reduced formulation consists in only four degrees of freedom, namely the wave, the macro-particle and the two boundaries, delimiting the portion of space occupied by the the uniform halo surrounding the inner bulk [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In the following subsection, we present recent studies on the equilibrium statistical mechanics of the Vlasov equation (and not of the N particle dynamics) [61,62,63], in the spirit of LyndenBell's work [1] in the context of self-gravitating stars.…”
Section: Kinetic Theories Of Systems With Long Range Interactionsmentioning
confidence: 99%
“…Such reduced formulation consists in only four degrees of freedom, namely the wave, the macro-particle and the two boundaries, delimiting the portion of space occupied by the the uniform halo surrounding the inner bulk, see Antoniazzi et al (2005) .…”
Section: Introductionmentioning
confidence: 99%
“…It can be therefore hypothesized that a significant reduction in the intensity fluctuations can be gained by implementing a dedicated control strategy, aimed at confining the macro-particle in space. In addition, the size of the macroparticle is directly related to the bunching parameter, a quantity of paramount importance in FEL context, see Antoniazzi and Fanelli (2005). Smith and Pereira (1978) showed that a test-wave, being characterized by a frequency close to the one of the wave, can effectively destroy the macroparticle and activate a consequent detrapping process.…”
Section: Introductionmentioning
confidence: 99%